2005
DOI: 10.1039/b502794b
|View full text |Cite|
|
Sign up to set email alerts
|

The synergic effect between Mo species and acid sites in Mo/HMCM-22 catalysts for methane aromatization

Abstract: The acid properties of Mo/HMCM-22 catalyst, which is the precursor form of the working catalyst for methane aromatization reaction, and the synergic effect between Mo species and acid sites were studied and characterized by various characterization techniques. It is concluded that Brønsted and Lewis acidities of HMCM-22 are modified due to the introduction of molybdenum. We suggest a monomer of Mo species is formed by the exchange of Mo species with the Brønsted acid sites. On the other hand, coordinate unsatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 48 publications
(63 reference statements)
0
16
0
Order By: Relevance
“…According to Ma et al . an ideal MDA catalyst should have an appropriate balance between the free Brønsted acid sites and acid sites with anchored Mo . By utilizing Mo/MCM‐22 with different Mo loading, they showed that the best catalyst possessed three Al per unit cell, where one framework Al was associated with aromatization reaction, while other two were used to anchor Mo.…”
Section: Topology Brønsted Acidity and The Aromatization Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Ma et al . an ideal MDA catalyst should have an appropriate balance between the free Brønsted acid sites and acid sites with anchored Mo . By utilizing Mo/MCM‐22 with different Mo loading, they showed that the best catalyst possessed three Al per unit cell, where one framework Al was associated with aromatization reaction, while other two were used to anchor Mo.…”
Section: Topology Brønsted Acidity and The Aromatization Reactionsmentioning
confidence: 99%
“…In conclusion, the separation of these functionalities is not possible . Although some studies address the optimal loading of Mo, given a zeolite with certain acidity and vice versa,,,,, the optimal proximity of BAS to Mo site and the optimal concentration of both sites per zeolite cage is only discussed for MCM‐22 . A careful study is necessary, both varying Mo/Al ratios as well as Si/Al ratios over a wide range while carefully characterizing how many well‐dispersed Mo sites are created inside the pores of the zeolite.…”
Section: A Bifunctional Catalyst and The Two‐step Mechanismmentioning
confidence: 99%
“…80% in maximum) as well as a better tolerance to carbonaceous deposits, as compared with Mo/HZSM-5 catalyst under the same experimental conditions [22] MCM-22 zeolite possesses two independent multidimensional channel systems, one system is two-dimensional 10-MR sinusoidal inter-layer channel systems, while the other is inter-layer channel systems contains 12-MR super-cages with inner free space of 0.71 Â 0.71 Â 1.82 nm [23]. The unique catalytic performance of the Mo/HMCM-22 catalyst is probably due to the unusual channel structure of HMCM-22 zeolite [22,24].…”
Section: Introductionmentioning
confidence: 97%
“…Actually, the synergistic effect between Brønsted acid sites and transition metal sites during reactions has been intensively investigated in the available literature. 6,7 However, it often shows complexity and specificity depending on different reactions and various catalyst systems.…”
Section: Introductionmentioning
confidence: 99%